Do Overconfidence and Herding Affect Stock Investment Decision? Indonesian Cases During Pandemic Covid-19 - Dewi Tamara (Universitas Mercu Buana, 2022)
Objective: To analyze the effect of overconfidence and herding on stock investment decision-making with risk perception as a mediating variable and financial literacy as a moderating variable.Methodology: The survey was launched and replied by 99 stock investors. The data is analyzed using Structural Equation Modeling with the software Smartpls 3.0.Findings: The results show that herding had a positive and significant effect on stock investment decisions. Overconfidence does not have either a direct or indirect effect on stock investment decisions. Risk perception also does not mediate overconfidence in stock investment decisions. The Herding variable has an effect on stock investment decisions. However, financial literacy does not moderate herding and stock investment decisions. This research contributes in several ways. Firstly, overconfidence is not proven to indirectly affect stock investment decisions through risk perception. In other words, risk perception does not have a mediation effect. Overconfidence also does not affect stock investment decisions directly. Secondly, herding affects stock investment decisions positively. Finally, financial literacy does not moderate herding and stock investment decisions.Conclusion: The result showed that there was a significant positive effect of herding on stock investment decisions. Risk perception does not mediate overconfidence and stock investment decisions. Financial literacy does not moderate herding and stock investment decisions. Overconfidence also does not have a relation to stock investment position. In this research, the stock investment decision is mostly influenced by herding.